The era of sustainable development and the challenge of climate change - Miró-Pérez, Albert-P. (2023)
Sustainability makes it possible to understand that the human being is facing a world with exhaustible resources and limited needs, with a population in constant growth and with economic progress based on obsolete technologies that generate a huge energy consumption, apart from billions of tons of wastes added to the ecosystem. These factors unleash catastrophic climatic consequences that have put the “world” on alert when is understood that there is a limit of planetary support capacity and that we are approaching the collapse of the ecosystem and endangering future generations, in addition to undermining the quality of life of all living beings because they exceed the capacity for natural balance of the ecosystems that support it. The increase in poverty, the overproduction of waste, the enormous North-South differences, the desertification and climate change are some of the main factors that human beings must face with great urgency. Regarding this last factor, it should be noted that today it has become a problem of multidimensional proportions that involves governments, organizations and entire societies with the aim of reducing its catastrophic global consequences and has been categorized as one of the greatest challenges of the world in the 21st century. Damage to the environment is becoming an issue that has received greater interest and attention over the years. Therefore, it is necessary a construct that includes ecological and development perspectives, that is, Sustainable Development. Under this context, this article aims to analyse in detail this concept, its origins and evolution, as well as its dimensions, to also establish its link with climate change, both inseparable factors.